2019
DOI: 10.1002/bab.1781
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic properties of dietary phenolic compounds: Inhibition effects on α‐amylase, aldose reductase, and α‐glycosidase

Abstract: Aldose reductase (AR), α‐amylase, and α‐glycosidase are vital enzymes to prevent diabetic complications. Here, AR was purified from sheep kidney using elementary methods with 111.11‐purification fold and with 0.85% purification yield. The interactions between some phenolic compounds and the AR, α‐glycosidase, and α‐amylase enzyme were determined. It was found that phenolic compounds exhibit potential inhibitor properties for these enzymes. For α‐amylase, studied phenolic compounds showed IC50 values in the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 47 publications
2
66
1
Order By: Relevance
“…According to other studies, phenolic compounds are showed inhibitory effects on AR and α-Gly enzymes activity. [5] This result is supported by the literature. According to the results, VCM administration may have increased oxidative stress in the kidney.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…According to other studies, phenolic compounds are showed inhibitory effects on AR and α-Gly enzymes activity. [5] This result is supported by the literature. According to the results, VCM administration may have increased oxidative stress in the kidney.…”
Section: Discussionsupporting
confidence: 85%
“…Aldose reductase (AR) is the rate-determining enzyme of polyol pathways, which possesses a significant role in the complications of diabetes, such as retinopathy, cardiovascular disease, neuropathy, cataract, and nephropathy. [5,6] Controlling blood glucose can prevent the improvement and progression of diabetic complications. AR inhibition is though oft as crucial prose for the prevention of diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the α-glycosidase inhibitory effect of Ag-NHC complex 1 was carried out using the p-nitrophenyl-D-glycopyranoside molecule (p-NPG) as the substrate according to the method of Tao et al [40] Samples of this work were prepared by dissolving as mg/mL. This assay was performed according to previous studies [41,42].…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…This pathway metabolizes the excess glucose, resulting in adverse impacts with raised mitogen-activated protein kinase, protein kinase C, oxidative, reductive, and glycative stress, and advanced glycation end products. [1][2][3] The polyol pathway in cells consists of two main enzymes. Aldose reductase (AR) is a monomeric oxidoreductase, which causes the reduction of glucose molecule to sorbitol using NADPH.…”
Section: Introductionmentioning
confidence: 99%